Pengembangan Media RUANG 3D (Rumah Gadang 3 Dimensi) Tema Lingkungan Sahabat Kita untuk Siswa Kelas V - Pandam Sri Wardhani; Ida Putriani; M.Iqbal Baihaqi (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2023)
The needs analysis indicates that thematic learning has not been using the appropriate media to facilitate content delivery, leading to a lack of enthusiasm among students in the learning process. This study aims to develop a suitable 3D SPACE media for Theme 8 Subtheme 1 learning. The research type is Research and Development (R&D) using the Borg and Gall model, which consists of nine steps. The research instruments used include interview guidelines, observation sheets, questionnaires, and documentation. The feasibility results from content experts are 91%, media experts 79%, and language experts 84%. Therefore, the 3D SPACE media is considered suitable for thematic learning. The student response questionnaire results indicate an average of 92%.